The Witnesses to the 20th Century. Melchior Wańkowicz – Józef Czapski - Nowacka, Beata (Porównania, 2025)
The article attempts to reconstruct the relationship between two important witnesses of the 20th century – Melchior Wańkowicz and Józef Czapski. The primary research material comes from the publications of both writers and their unpublished letters. Wańkowicz was a reporter and chronicler of Polish memory places. Czapski was a writer, painter and soldier who survived the Katyn massacre and a co-founder of the “Kultura” Literary Institute near Paris. The text tells the story of the bond between two great personalities who did not choose their fate but consciously accepted it and, with great effort, shaped it, responsibly using the resources that it had given them. The conclusion of the article is as follows: the bond between the two writers connected by some shared profound life experiences is not necessarily a strong one. However, in moments of occasional encounters, it is important for both of them and undoubtedly deep.